TARJIMASHUNOSLIK YO'NALISHIDA INNOVATSION G'OYALAR («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article analyzes innovative ideas in the field of translation studies.The research covers the latest innovations in the field of translation studies, translation technologies and translator training. The article considers issues such as improving the quality of translation, improving the skills of translators, and automating the translation process. New trends and future prospects in the field of translation were also discussed. In the conclusion, recommendations are given for the introduction and development of innovative approaches in the field of translation studies.